(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The concept of the flipped classroom has received significant attention, yet there’s been limited exploration of research into its implementation in English teaching, which is where this study steps in.The aim is to (1) explore the general responses of English teachers towards the flipped classroom methodology and (2) investigate the perceived benefits and challenges of its implementation in English teaching.A total of 10 English teachers from diverse institutions that have adopted the flipped classroom model participated in this research study. We used a combination of questionnaires and interviews to collect the data, and then subjected it to analysis using a range of techniques.The results were amazing! English teachers had a really positive response to the flipped classroom methodology. The benefits identified include facilitating active learning, developing collaborative teamwork, stimulating autonomous learning, and increasing classroom interaction. The challenges faced during its implementation pertained to the provision of support, technical and technological issues, and the development of flipped learning materials.